2012
DOI: 10.1093/mutage/ges005
|View full text |Cite
|
Sign up to set email alerts
|

Genomic instability induced by  -pinene in Chinese hamster cell line

Abstract: Here, we report the effects of exposure of mammalian cells to α-pinene, a bicyclic monoterpene used in insecticides, solvents and perfumes. Morphological analysis, performed in V79-Cl3 cells exposed for 1 h to increasing concentrations (25 up to 50 μM) of α-pinene, indicated a statistically significant increase in micronucleated and multinucleated cell frequencies; apoptotic cells were seen at 40 and 50 μM. This monoterpene caused genomic instability by interfering with mitotic process; in fact, 50% of cells (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 25 publications
(26 reference statements)
0
20
1
2
Order By: Relevance
“…Most importantly, α-pinene was very effective in the treatment of experimental metastatic melanoma, reducing the number of lung tumor nodules. These findings indicate that α-pinene may inhibit cell proliferation by inducing cell apoptosis (Catanzaro et al, 2012). However, results from the present study showed that α-pinene did not induce BEL-7402 cell apoptosis.…”
Section: Discussioncontrasting
confidence: 88%
“…Most importantly, α-pinene was very effective in the treatment of experimental metastatic melanoma, reducing the number of lung tumor nodules. These findings indicate that α-pinene may inhibit cell proliferation by inducing cell apoptosis (Catanzaro et al, 2012). However, results from the present study showed that α-pinene did not induce BEL-7402 cell apoptosis.…”
Section: Discussioncontrasting
confidence: 88%
“…Several biological activities were attributed to terpinolene, such as anticancer (Harada et al, 2012), antioxidant (Dorman, Figueiredo, Barroso, & Deans, 2000), antifungal (Hammer, Carson, & Riley, 2004) and larvicidal (Conti et al, 2012) activities. to the V79-Cl3 cell culture, suggesting that this compound is able to compromise genome stability preferentially through mitotic alterations and damage DNA through ROS production (Catanzaro et al, 2012). The presence of α-pinene, although in lower concentrations among the major compounds of the EO from M. atropurpureum, could explain the reduced motility and sperm membrane functionality due to oxidative damage of sperm membrane and mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthy, MO or mastic water extract were previously shown to lack genotoxic or mutagenic activities 43, 44 . Many studies also demonstrated lack of genotoxicity for β-myrcene or α-pinene in in vitro and in vivo systems 4548 however, in one study α-pinene was shown to compromise genomic instability 49 . Notably, various monoterpenes such as limonene and perillic acid have been reported to possess antitumor activity 10 .…”
Section: Discussionmentioning
confidence: 99%